115k views
4 votes
Y = -x + 7 substitution methody = 2x + 7

1 Answer

1 vote

The given system of equation:

y = -x + 7 (1)

y = 2x + 7 (2)

Apply substitution method to solve for x & y

Substitute the value of y from the equation(2) into equation(1)

y = 2x + 7

-x + 7 = 2x + 7

7 - 7 = 2x + x

3x = 0

x = 0

Now, susbtiute the value of x = 0, in the equation (1)

y = - x + 7

y = -(0) + 7

y = 7

So, the solution of the system of equation is : (x, y) = (0, 7)

Answer : (x,y) = (0,7)

The graph will be :

User Richard Edwards
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.